Improving wear and corrosion protection of AISI 304 stainless steel by Al2O3-TiO2 hybrid coating via sol-gel process - Gecu, Ridvan; Birol, Burak; Ozcan, Mucahid (TAYLOR & FRANCIS LTD, 2022)
Al2O3, TiO2, and Al2O3-TiO2 coatings were deposited on AISI 304 stainless steel plates by the sol-gel dipping technique, and the effects of the coating composition on microstructure, wear, and corrosion characteristics were examined. Tribological features were determined by ball-on-disc sliding tests against an Al2O3 ball under a 10 N load, while corrosion properties were evaluated by potentiodynamic polarisation tests performed in 3.5% wt. NaCl solution. gamma -Al2O3, alpha -Al2O3, and rutile phases were detected in the hybrid coatings. The highest coating thickness was obtained in single Al2O3 film and decreased with an increasing amount of TiO2 nanoparticles. The single Al2O3 layer had both the highest wear resistance and the lowest corrosion resistance. Although TiO2 addition caused an increase in the wear rate, it improved the corrosion resistance of the coating by filling the voids in the Al2O3 film. The Al2O3-TiO2 hybrid film with a relative ratio of 6:1 as a candidate for the wear- and corrosion-resistant coating decreased wear and corrosion losses of the 304 substrates by 83% and 97%, respectively.
Keywords: Al2O3-TiO2 hybrid coating; sol-gel; wear; corrosion; AISI 304 stainless steel; 316L STAINLESS-STEEL; MULTILAYER COATINGS; OPTICAL-PROPERTIES; SLIDING WEAR; TIO2; BEHAVIOR; LAYER; FILM; MICROSTRUCTURE; ENHANCEMENT; Electrochemistry; Metallurgy & Metallurgical Engineering; Materials Science